2015
DOI: 10.4028/www.scientific.net/amr.1113.230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Identification of Isolated Microorganism from Agricultural Soil for Degradation of Cellulose Based Waste

Abstract: Paper wastes accumulating in the environment are posing an ever increasing ecological threat. This study aimed to isolate soil bacteria closely associated with the bacteria degrading waste paper. A total of six soil samples were collected from dumped soil hostel garden at Universiti Teknologi MARA, Shah Alam. Bacillus, Aspergillus and Micrococcus species were found to be the most widely distributed on the entire sample taken. Six cultures were screened for the ability to degrade cellulose. Bacillus was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…has the ability to reduce oxidative damages by radicals. Furthermore, another study revealed that the extract of Micrococcus lutues containing hexahydro- (2) and pyrrolo[1,2a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl)- (3) exhibited promising cytotoxic effect on HCT15 with (Abdullah et al, 2015 ). Thus, it was suggested that both of the identified pyrrolopyrazine could have contributed the antioxidant and anticancer activities observed in MUM256 extract.…”
Section: Resultsmentioning
confidence: 99%
“…has the ability to reduce oxidative damages by radicals. Furthermore, another study revealed that the extract of Micrococcus lutues containing hexahydro- (2) and pyrrolo[1,2a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl)- (3) exhibited promising cytotoxic effect on HCT15 with (Abdullah et al, 2015 ). Thus, it was suggested that both of the identified pyrrolopyrazine could have contributed the antioxidant and anticancer activities observed in MUM256 extract.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic examination of the slides was done with a microscope using the oil immersion (×100) lens. Biochemical tests such as indole, hydrogen sulphide, catalase, citrate, methyl red, and sugar fermentation tests were also performed according to established procedures [31,32].…”
Section: Identification Of Isolatesmentioning
confidence: 99%